1983
DOI: 10.1080/00268978300102081
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio CI study of the ground and excited states of p-benzoquinone

Abstract: Configuration interaction (C I) studies of ground, n ~r*, ~ ~r* electronically excited singlet and triplet states and of the ionized states (cations) are reported for p-benzoquinone. The splittings between two nrt* states, both for singlet and triplet, are shown to be very small confirming recent experimental results. A lower lying ~rTr* triplet state (aBz.) has been thereby assigned. The photoelectron spectra (PES) for the low-energy ionization region have been assigned. Contrary to the MO ordering, 2b3g(Tr.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…The decrease of the splitting between the odd and even T orbital combinations with the number of intervening (+ bonds is much slower than the decrease for two equally spaced ethylene molecules (defining the throughspace interaction in that case) at the corresponding distances. The predictions by the simple extended Huckel method or other semiempirical methods appear to be qualitatively correct and are not much changed when advanced methods are employed [7,16- Very accurate calculations on p-benzoquinone were also done without consideration of the lone-pair relaxation effect [27,28]. In a recent paper we found that the physical mechanism for the splitting inp-benzoquinone is simple and the erratic behavior often found in calculations due to a canceling of almost equal contributions [24].…”
Section: Introductionmentioning
confidence: 94%
“…The decrease of the splitting between the odd and even T orbital combinations with the number of intervening (+ bonds is much slower than the decrease for two equally spaced ethylene molecules (defining the throughspace interaction in that case) at the corresponding distances. The predictions by the simple extended Huckel method or other semiempirical methods appear to be qualitatively correct and are not much changed when advanced methods are employed [7,16- Very accurate calculations on p-benzoquinone were also done without consideration of the lone-pair relaxation effect [27,28]. In a recent paper we found that the physical mechanism for the splitting inp-benzoquinone is simple and the erratic behavior often found in calculations due to a canceling of almost equal contributions [24].…”
Section: Introductionmentioning
confidence: 94%
“…Computed excitation energies exhibit significant deviations from the experimental data in certain cases, even when computationally demanding procedures, like MRSDCI, are used. 11 Surprisingly, the important valence transition responsible for the prominent peak detected at 7.1 eV has not been yet studied with ab initio methods. No theoretical information about Rydberg states is available.…”
Section: Introductionmentioning
confidence: 99%
“…10 Inclusion of additional correlation effects through the MRSDCI procedure did not change the conclusion. 11 In this paper, we present an extensive ab initio study of the electronic transitions of p-benzoquinone in order to answer the unresolved questions and to give quantitatively reliable vertical excitation energies for the main valence and Rydberg states. The multiconfigurational second-order perturbation ͑CASPT2͒ method [17][18][19] has been used for the calculation of the electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…1971;Lauer etal. 1975;Kobayashi 1975;Wood 1975;Dougherty and McGlynn 1977;Bigelow 1978;Bloor et al 1979;Asbrink -et al 1979;Jacques et al 1981;Ha 1983; for a discussion and detailed references see von ). The two lowest energy 1T ionisations 2b 3u (1T +) and Ib 1gC1T _) and the two oxygen lone pair orbitals 3b3in+) and 4b 2u (n_) are to be found in an interval barely exceeding 1 eV.…”
Section: Application Of the Adc(3) Methods To N2mentioning
confidence: 99%